The ambiguity of the definition of arabic sentence - Mfreg, Hasan Mohammed (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to highlight the effect of theoretical grammatical disturbance in the definition of the sentence on the applied side, and the researcher followed the descriptive approach; Describe the attempts of the grammarians to define the sentence and then indicate the effect. The definition of the Arabic sentence has passed through several stages until it was settled by the late grammarians about whom I conveyed that they had distinguished between the sentence and the utterance. The first of them requires attribution without the requirement of being meaningful while the latter requires attribution beside being meaningful. However, this agreement on the definition of the term did not remove the ambiguity of the concept, which was evident in the application at the level of sentences analysis or the composition of a text. At the level of sentences analysis, there were a lot of disagreements about counting sentences and identifying their boundaries in a specific text. As for the composition of a text, there are a great confusion about identifying the end of each sentence.